Student interaction with ChatGPT can promote complex critical thinking skills - Suriano, Rossella; Plebe, Alessio; Acciai, Alessandro; Fabio, Rosa Angela (Learning and instruction, 2025)
The widespread adoption of AI-based chatbots has revolutionized the interaction between individuals and machines, providing personalized and immediate responses. Within the educational sector, students increasingly rely on ChatGPT to address academic challenges, but the consequences of this interaction on critical thinking abilities are not well understood. This study aims to explore the relationship between factors such as attitudes and trust towards AI, engagement, knowledge, and the ability to solve complex critical thinking in a sample of Italian students. Two hundred and thirteen students completed self-report questionnaires and performance measures on the Critical Reasoning Assessment. The results highlighted significant relationships among the variables considered, emphasizing a direct impact of attitude and trust on knowledge and engagement with AI. Furthermore, engagement proved to have a particularly significant impact on critical thinking performance compared to knowledge. These findings are relevant in the educational context, suggesting that interaction with AI-based chatbots can be a valuable resource for the development of students' critical thinking skills. However, it is emphasized the importance of adopting an educational approach that fosters active engagement and in-depth understanding to promote the critical analysis of information provided by AI-based chatbots. •Attitude and trust towards AI directly influencing user knowledge and engagement.•Knowledge and engagement with AI can influence critical thinking abilities.•Responsibly using ChatGPT in education can promote critical thinking.